The Effects of Non-ischemic Fibrosis Texture and Density on Mechanisms of Reentry - Balaban, Gabriel; Halliday, Brian P.; Costa, Caroline Mendonca; Porter, Bradley; Bai, Wenjia; Plank, Gernot; Rinaldi, Christopher A.; Rueckert, Daniel; Prasad, Sanjay K.; Bishop, Martin J. (Computing in Cardiology, 2018)
Patients who present with non-ischemic dilated cardiomyopathy and enhancement on late gadolinium magnetic resonance imaging (LGE-CMR), are at high risk of sudden cardiac death. Further risk stratification of these patients based on LGE-CMR may be improved through better understanding of fibrosis micro-structure. Our aim is to examine variations in fibrosis micro-structure based on LGE imaging, and quantify the effect on reentry in-ducibility. 2D Computational models were created from a single short axis LGE-CMR image, with variations in fibrosis type (interstitial, replacement) and density. For each fibrosis-type density combination 10 different models were created, each representing a separate random realization. In total 200 models were tested. Reentry inducibility showed a dependence on fibrosis type and density as well as on the specific random realization of the type-density combination.
CRIS-Team Scopus Importer:2023-03-08